Model Regresi Data Panel Robust terhadap Kemiskinan di Provinsi Sulawesi Selatan - Mahrani; Elisabeth Evelin Karuna; Atiqa Azza El Darman (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Poverty is one of the fundamental issues in socio-economic development in Indonesia, which remains the main focus of regional policies. Variations in poverty levels between districts/cities in South Sulawesi Province reflect differences in development performance influenced by economic growth and the Human Development Index (HDI). This article aims to analyze the influence of these two factors on poverty using a Panel Data Regression approach with Heteroskedasticity-Consistent Estimator (Robust Standard Errors). Theoretically, this method was developed to produce parameter estimates that remain consistent even when classical assumptions are violated, particularly heteroskedasticity and cross-section unit correlation. The data used covers 24 districts/cities in South Sulawesi Province during the 2020–2024 period. The analysis was conducted using Fixed Effect (FE) and Random Effect (RE) models, accompanied by a Hausman test to determine the best model, as well as Pesaran CD, Breusch-Pagan LM, and Wooldridge diagnostic tests. The results of the article show that HDI has a negative and significant effect on poverty levels, while economic growth has no significant effect. The robust approach has been proven to increase the reliability of estimation results in socioeconomic data conditions that do not meet the assumption of homoscedasticity. These findings indicate that improving the quality of human resources through education and health is a key strategy in reducing poverty levels in South Sulawesi. Abstrak. Kemiskinan merupakan salah satu persoalan fundamental dalam pembangunan sosial ekonomi di Indonesia yang masih menjadi fokus utama kebijakan daerah. Kemiskinan di Provinsi Sulawesi Selatan masih menunjukkan variasi antarwilayah yang dipengaruhi oleh pertumbuhan ekonomi dan Indeks Pembangunan Manusia (IPM). Penelitian ini menganalisis pengaruh kedua variabel tersebut menggunakan regresi data panel dengan Driscoll–Kraay Robust Standard Errors, yang dipilih karena mampu mengatasi heteroskedastisitas, autokorelasi, dan cross-sectional dependence. Data mencakup 24 kabupaten/kota selama periode 2020–2024. Model Fixed Effect (FE) dan Random Effect (RE) diuji, dan pemilihan model dilakukan menggunakan uji Hausman. Hasil penelitian menunjukkan bahwa IPM berpengaruh negatif dan signifikan terhadap kemiskinan, sementara pertumbuhan ekonomi tidak signifikan. Pendekatan robust ini meningkatkan reliabilitas hasil estimasi dan memberikan gambaran empiris yang relevan bagi kebijakan pengentasan kemiskinan di Sulawesi Selatan. Artikel ini menggunakan metode Regresi Data Panel dengan Driscoll–Kraay Robust Standard Errors untuk memastikan konsistensi standard error ketika terjadi heteroskedastisitas dan cross-sectional dependence. Analisis mencakup 24 kabupaten/kota di Provinsi Sulawesi Selatan periode 2020–2024 menggunakan model Fixed Effect (FE), Random Effect (RE), dan Uji Hausman. Hasil menunjukkan bahwa IPM berpengaruh negatif dan signifikan terhadap kemiskinan, sementara PDRB tidak berpengaruh signifikan. Pendekatan Driscoll–Kraay meningkatkan reliabilitas estimasi dibanding robust konvensional.